2010
DOI: 10.1542/peds.2010-0791
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of Controlled Medications to Adolescents and Young Adults in the United States

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The nonmedical use of prescription drugs by adolescents and young adults has surpassed all illicit drugs except marijuana and has become an increasing public health concern. Adolescents and young adults are in the most likely age groups to abuse prescription medications. WHAT THIS STUDY ADDS: OBJECTIVE:The nonmedical use of prescription drugs by adolescents and young adults has surpassed all illicit drugs except marijuana, yet little is known about prescribing patterns. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
152
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(162 citation statements)
references
References 25 publications
7
152
0
3
Order By: Relevance
“…Consistent with prior studies, 2,4 we found that black patients were prescribed opioids less frequently than white patients for moderate to severe pain in the emergency setting. This relationship remained consistent across each aspect of neighborhood-level SES, while accounting for other factors including pain level, type of visit, age, gender, frequency of prior ED visits, and hospital location.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with prior studies, 2,4 we found that black patients were prescribed opioids less frequently than white patients for moderate to severe pain in the emergency setting. This relationship remained consistent across each aspect of neighborhood-level SES, while accounting for other factors including pain level, type of visit, age, gender, frequency of prior ED visits, and hospital location.…”
Section: Discussionsupporting
confidence: 90%
“…Based on prior literature, we included patient race, ethnicity, gender, patient age, pain severity, region of country, hospital location (urban/ Metropolitan Statistical Areas (MSA)), hospital ownership, and whether the visit was related to an injury or trauma in our models. 2,4 To control for whether a patient was a frequent visitor to the ED, we also included the frequency of prior visits to the ED within the past year and whether the patient had been seen in the ED within the past 72 hours. All covariates were included based clinical significance and statistical significance in bivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations